Optimalisasi Potensi Lokal melalui Pelatihan Batik Pewarna Alam: Langkah Menuju Kemandirian dan Keberlanjutan Ekonomi Remaja Marginal - Utama, Agung; Mustikasari, Anita; Hariningsih, Endang; Endarwati, Maria Lies; Hastuti, Purwanti Widhy (Universitas Nusantara PGRI Kediri, 2024)
The batik-making skills training program using natural dyes from waste materials for marginalized youth in Wijirejo Village, Bantul, aims to enhance participants' skills, economic independence, and business sustainability. This program is supported by Nonalia Batik SMEs and the community service team from Yogyakarta State University. The training methods include entrepreneurship theory, batik-making practice, and small business management assistance, including digital marketing. Evaluation results show significant improvements in participants' skills, with some successfully starting their own batik businesses and increasing their income. This program has had a positive impact on the local economy and empowered marginalized youth within their communities.